2024
DOI: 10.1177/21582440241228920
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Students for Cybersecurity Awareness Management in the Emerging Digital Era: The Role of Cybersecurity Attitude in the 4.0 Industrial Revolution Era

Bulbul Ahamed,
Mohammad Rashed Hasan Polas,
Ahmed Imran Kabir
et al.

Abstract: The purpose of the study is to examine how cybersecurity knowledge, password security, and self-perception of skill affect cybersecurity awareness issues via the mediating lens of cybersecurity attitude among university students in Bangladesh. A sample of 430 university students from two public and three private universities provided the data in Dhaka, Bangladesh. An approach known as stratified random sampling was used in this cross-sectional study. The positivist approach was used, and a hypothetical statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The importance of cybersecurity awareness has also been the topic of several previous studies [25], [26], [27], [28]. For example, first, [28] found that internet users in Israel, Slovenia, Poland, and Turkey have adequate cybersecurity awareness but apply minimal protective measures.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…The importance of cybersecurity awareness has also been the topic of several previous studies [25], [26], [27], [28]. For example, first, [28] found that internet users in Israel, Slovenia, Poland, and Turkey have adequate cybersecurity awareness but apply minimal protective measures.…”
Section: Literature Reviewmentioning
confidence: 97%
“…This suggests that tailored training programs are necessary due to country-specific differences impacting the relationships among awareness, knowledge, and behavior. Second, [27] found that internet users in Slovenia, Poland, and Turkey have adequate cybersecurity awareness but apply minimal protective measures. This suggests that tailored training programs are necessary due to country-specific differences impacting the relationships among awareness, knowledge, and behavior.…”
Section: Literature Reviewmentioning
confidence: 99%